Bank Sebagai Institusi Publik Analisis Hukum Atas Pendirian Dan Mekanisme Pembubaran Di Indonesia - Herliana Heltaji; Ayyub Kadriah; Dimas Aditya Pamungkas (Journal of Innovative and Creativity, 2025)
This study examines the relationship between the public functions of banks and the legal regime governing their establishment and dissolution in Indonesia. Banks are not merely commercial entities; they also serve as public institutions that safeguard financial system stability, protect public funds, and ensure the smooth operation of payment systems. The research employs a normative analysis method with conceptual and critical approaches, utilizing primary, secondary, and tertiary legal sources, as well as literature and online sources. The study focuses on: first, how the public functions of banks shape the legal framework for their establishment, distinguishing them from private corporations; second, how the systemic nature of banks necessitates authoritative dissolution mechanisms through resolution and special liquidation regimes. Findings indicate that bank establishment and dissolution regulations in Indonesia are inseparable from the objectives of economic stability and public trust, and that domestic legal literature requires stronger integration of macroeconomic and juridical perspectives. This study offers practical contributions for regulators and the banking industry while enriching academic discourse on bank intermediation as a public instrument.